A small scale study on small group interaction in enhancing writing skill among the form 3A students at SMK Paku, Bau / Pojen Minos - Minos, Pojen (2004)
The purpose of this small scale study is to test the effectiveness of small group interaction in enhancing writing skill among the Form 3A students of SMK Paku, Bau. The small scale study is trying to compare the marks obtained by the respondents who accomplished their writing task in a small group with interaction (experimental group) with the respondents who write individually after the teacher’s instructions (control group). The study involves two groups of respondents (the control and the experimental groups), 15 respondents in each group. The data of the study is obtained from the result of the pre and post tests as well as a set of questionnaires. The same type of writing test papers that include a picture or a picture series are given to both the control and experimental groups during the pre test. During the post test another set of the same type of writing test papers are given to the control and experimental groups again. After analyzing the data it is found that there is a salient contrast between the score of the respondents in the control and experimental groups during the post test. Besides, questionnaires are used to elicit responses from the respondents in the experimental group regarding their perceptions towards writing in a small group with interaction among the peers. The contrast of the score also occurs between low versus low proficiency learner in both groups and between high versus high proficiency learner in both groups during the post test. The salient contrast in the scores during the post test is hoped to be able to serve as a basis and can be used for relevant research in the future.